2008
DOI: 10.1007/s00300-008-0529-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of faecal glucocorticoid metabolites in Upland Geese Chloephaga picta

Abstract: Glucocorticoid (GC) hormones rise in response to stressors, including natural events including weather or predator presence, and human activities, such as hunting, scientiWc research or recreational visits. However, because blood sampling itself causes stress and is dangerous or even impossible in some wildlife species, feedback-free methods for GC determination are needed to assess stress in these animals. Faecal GC analyses have thus gained interest. Here, we validate a non-invasive method to estimate the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(18 reference statements)
1
6
1
Order By: Relevance
“…Although in birds, renal and faecal matter are jointly excreted via the cloaca [ 50 ], the turn-over time of corticosterone in uric acid is faster than from faecal matter, suggesting that the first peak (11:00–11:15) reflects corticosterone metabolites from uric acid, and the second peak (12:30–12:45) might be a sign of corticosterone metabolites from faecal excretion. This is consistent with data found in other goose and sheldgoose species [ 56 , 65 , 66 ].…”
Section: Resultssupporting
confidence: 93%
“…Although in birds, renal and faecal matter are jointly excreted via the cloaca [ 50 ], the turn-over time of corticosterone in uric acid is faster than from faecal matter, suggesting that the first peak (11:00–11:15) reflects corticosterone metabolites from uric acid, and the second peak (12:30–12:45) might be a sign of corticosterone metabolites from faecal excretion. This is consistent with data found in other goose and sheldgoose species [ 56 , 65 , 66 ].…”
Section: Resultssupporting
confidence: 93%
“…A subsample of 0.08 g of dried samples was mixed with 1 ml double-distilled water, to compensate for the water loss during drying (see Koch et al 2009 ), and 1.5 ml methanol before vortexing for 30 min. Ethanol samples were dried using a STERIS Lyovac GT-2E freeze dryer and then treated like dried samples (see above).…”
Section: Methodsmentioning
confidence: 99%
“…However, as glucocorticoids are metabolised in a species-specific manner before excretion and assays need to be validated for each species, we wanted to test whether these findings from studies in primates may be transferred to an avian system. A previous study by Koch et al ( 2009 ) on captive Upland geese showed that the concentrations of corticosterone metabolites (CM) of frozen and dried samples were highly correlated, indicating that the collection of droppings followed by drying might be an easy way to prepare samples for transport during fieldwork. However, Koch et al ( 2009 ) used a freeze-dryer, equipment that is not necessarily available under fieldwork conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure plasma indices, a blood sample is required but non-invasive techniques (e.g. samples from faeces) have also been used in geese (Koch et al, 2009). Caution is required in the interpretation of stress responses because large and consistent individual differences are seen in the way that individual animals deal with stressors and these have recently been demonstrated in geese (Pisa et al, 2006;Kralj-Fiser et al, 2010).…”
Section: Fear and Distress During Feather Collection In Geesementioning
confidence: 99%